IDENTIFICATION OF PHYSICOCHEMICAL PROPERTIES, PHARMACOKINETICS AND TOXICITY OF ACTIVE COMPOUNDS OF Kaempferia galanga RHIZOME - Laili Nailul Muna (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
The Kencur plant has many benefits, is economically valuable, and is widely cultivated by the local community. The development of kencur compounds has not been carried out optimally because of the relatively high cost of identifying the content of each compound. This study aimed to determine the physiochemical properties of kencur compounds and their pharmacokinetics, as well as the toxicity of the herb kencur rhizome in silico. The method used in this study uses a Marvin sketch to draw the structure of the compound, which was then analyzed using Lipinski to determine its physico-chemical properties. Pharmacokinetic and toxicity analyses were performed using the pKCSM software. The results showed that all compounds followed Lipinski's rules; therefore, predictably, they could be developed into drug molecules from these compounds. In addition, all compounds had fairly high Water Solubility (log S). All HIA compounds were >90%, so they were well absorbed in the intestine and showed good permeability to CaCO-2 with a log Papp value of > 0.90. All the above compounds have low permeability to the skin due to the log Kp value > -2.5, so they are not suitable for transdermal preparations. Keywords: Physicochemistry, Pharmacokinetics, Toxicity, Kencur, In silico